Kleinhovia hospita extract alleviates experimental hepatic and renal toxicities induced by a combination of antituberculosis drugs - Yulia Yusrini Djabir; Aryadi Arsyad; Mufidah Murdifin; Rosany Tayeb; Muhammad Nur Amir; Fatwa Al-Fia Kamaruddin; Nurul Husna Najib (Shahrekord University of Medical Sciences, 2021)
Introduction: Antituberculosis drugs are associated with hepatic and renal toxicities due to drug's radical metabolites. Kleinhovia hospita L extract possesses a potent antioxidant capacity that can be beneficial in eradication of oxidative-induced cell damage. This study aimed to evaluate the effects of K. hospita hydro-alcoholic extract on biomarkers and structure changes in liver and kidney induced by a combination of antituberculosis drugs (CAD), comprising isoniazid, rifampicin, pyrazinamide and ethambutol in Wistar rats. Methods: Thirty-five male Wistar rats were assigned into one of the five groups: control, CAD, and CAD with K. hospita extract in three different doses (125, 250 and 500 mg/kg). The extract was administered three hours prior to CAD and all treatments were carried out for 28 days. Following the last day of treatment, blood samples and organs were collected for biomarker analysis and histopathological examinations. Results: Twenty-eight days of CAD treatment in rats induced marked elevation of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), serum creatinine and urea levels compared to controls. K. hospita extract at higher doses (250 mg/kg and 500 mg/kg) significantly improved ALT, urea and creatinine levels in the rats treated with CAD (P<0.05), although it did not significantly reduce AST. Furthermore, liver and renal tissue damages induced by CAD were restored with K. hospita extract treatment, especially at higher doses. Conclusion: Kleinhovia hospita extract treatment has the potential to protect the liver and renal damage induced by toxic doses of CAD.